Brachytherapy for malignancies of the vagina in the 3D era - Glaser, Scott M.; Beriwal, Sushil (Journal of Contemporary Brachytherapy, 2015)
Vaginal cancer is an uncommon malignancy and can be either recurrent or primary. In both cases, brachytherapy places a central role in the overall treatment course. Recent technological advances have led to more advanced brachytherapy techniques, which in turn have translated to improved outcomes for patients with malignancies of the vagina. The aim of this manuscript is to outline the incorporation of modern brachytherapy into the treatment of patients with vaginal cancer including patient selection along with the role of brachytherapy in conjunction with other treatment modalities, various brachytherapy techniques, treatment planning, dose fractionation schedules, and normal tissue tolerance.